(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article presents information and opinions on the organization of play activities of preschool children in educational centers. An attempt was also made to explain in detail the features and important aspects of gaming activities in development centers.